Initial tacrolimus weight-based dosing strategy in allogeneic hematopoietic stem-cell transplantation. (August 2021) - Soskind, Rose; Xiang, Elaine; Lewis, Tyler; Al-Homsi, A. Samer; Papadopoulos, John; Cirrone, Frank
Tacrolimus is a mainstay medication for graft-versus-host disease (GVHD) prophylaxis in combination with other immunosuppressive agents. Achieving therapeutic tacrolimus levels is vital in preventing acute GVHD (aGVHD), while supratherapeutic levels may increase risk of toxicity and relapse. We performed a single center retrospective chart review including all adult patients post-allogeneic hematopoietic stem-cell transplantation who received initial tacrolimus continuous intravenous infusion for GVHD prophylaxis between June 1, 2017 and December 31, 2019. The primary outcome was the percent of patients with an initial therapeutic tacrolimus level, defined as 5–12 ng/mL, after empiric weight-based dosing at 0.02 mg/kg/day. Secondary outcomes included evidence of tacrolimus toxicity within seven days of initiation, incidence of aGVHD by day 100, and relapse after six months. An initial therapeutic level was achieved in 47% of patients with a median initial level of 12.4 ng/mL. Fifty-two percent of patients had supratherapeutic levels. No significant nephrotoxicity, hepatotoxicity, or neurotoxicity occurred within a week of starting tacrolimus or at neutrophil engraftment. Grade II-IV aGVHD by day 100 was observed in 22% of patients, and relapse after six months was found in 16% of patients. These results have led to consideration of an empiric 20% dose reduction to 0.016 mg/kg/day or an expanded initial tacrolimus target of 5–15 ng/mL as there was low aGVHD incidence and no increased risk of toxicity.